2009
DOI: 10.1007/bf03178336
|View full text |Cite
|
Sign up to set email alerts
|

The characterisation of a novelPichia anomala β-glucosidase with potentially aroma-enhancing capabilities in wine

Abstract: -The production and characterisation of β-glucosidase from an isolated yeast strain classified as a Pichia anomala MDD24 were studied. The result shows that cellobiose is a good inducer for extracellular β-glucosidase production and optimum concentration is 1.5 percent cellobiose in yeast peptone dextrose medium. The purified β-glucosidase from Pichia anomala MDD24 exhibited a specific activity of 614 ± 14 U mg -1 of protein and a molecular mass of 42 kDa. This enzyme was slightly inhibited by fructose and suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 36 publications
(43 reference statements)
3
33
0
4
Order By: Relevance
“…The b-glucosidases can play a key role in the release of volatile grape aromas and their activities have been extensively researched in wine yeast (Rodriguez et al 2004). Although some activity in difference strains of Saccharomyces cerevisiae has been described (Mateo and Di Stefano 1997;Hernandez et al 2002;Restuccia et al 2002;Spagna et al 2002a), most studies found higher b-glucosidase producers among non-Saccharomyces species (Gueguen et al 1995;Yanai and Sato 1999;Fernandez et al 2000;Manzanares et al 2000;Ferreira et al 2001;Strauss et al 2001;Spagna et al 2002b;Cordero Otero et al 2003;Wallecha and Mishra 2003;Rodriguez et al 2004 andArevalo Villena et al 2005;Swangkeaw et al 2009). The two yeast strains isolated from grape and tropical fruits grown in Thailand support those findings.…”
Section: Discussionmentioning
confidence: 93%
“…The b-glucosidases can play a key role in the release of volatile grape aromas and their activities have been extensively researched in wine yeast (Rodriguez et al 2004). Although some activity in difference strains of Saccharomyces cerevisiae has been described (Mateo and Di Stefano 1997;Hernandez et al 2002;Restuccia et al 2002;Spagna et al 2002a), most studies found higher b-glucosidase producers among non-Saccharomyces species (Gueguen et al 1995;Yanai and Sato 1999;Fernandez et al 2000;Manzanares et al 2000;Ferreira et al 2001;Strauss et al 2001;Spagna et al 2002b;Cordero Otero et al 2003;Wallecha and Mishra 2003;Rodriguez et al 2004 andArevalo Villena et al 2005;Swangkeaw et al 2009). The two yeast strains isolated from grape and tropical fruits grown in Thailand support those findings.…”
Section: Discussionmentioning
confidence: 93%
“…In our previous research, F6 had been determined to be an extracellular β‐glucosidase producer when cultured in a basal medium (Wang and others 2011a). A large array of yeast has been reported to produce β‐glucosidase with varying potentials (Swangkeaw and others 2009; Barbosa and others 2010). Among these β‐glucosidases, the β‐glucosidase from F6 is novel β‐glucosidase with more impetus for commercial application, especially during the winemaking process.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, β‐glucosidases from grapes and other fruits generally appear to have low activity under winemaking conditions. They are not active between pHs 3.0 and 4.0 and are inhibited by sugars (Swangkeaw and others 2009). Thus, to increase wine aroma, it is necessary to use cellular or acellular form of the enzyme from microbial strains (Otero and others 2003; Barbagallo and others 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Terpene production was observed in Muscat-type grape juice and wine treated with β-D-glucosidase from P. anomala MDD24 [53,54]. This glucosidase was efficient in releasing desirable aromas particularly during the final stage of alcoholic fermentation due to its tolerance to high concentrations of ethanol.…”
Section: W Anomalus Is a Good Producer Of Relevant Enzymes For Winemmentioning
confidence: 99%